Evaluación del comportamiento poscosecha de dos métodos de aplicación de ozono en tomate riñón (Solanum lycopersicum, L.), cosechado a diferentes índices por color, Cotopaxi, período 2020 – 2021 - Mañay Maisanche, Natalia Catalina (2021)
The present research was carried out in the Chimbacalle neighborhood, Mulalillo parish, Canton Salcedo, Province of Cotopaxi, at an altitude of 2757 m.a.s.l. with a longitude of 78°37'19” west and latitude of 0° 59'47” south, with the aim of evaluating the postharvest behavior of two ozone application methods in kidney tomato (Solanum lycopersicum, L.) harvested at different indexes by color. A complete random design was applied with a factorial arrangement of 4 x 2 x 3, giving a total of 24 treatments and 72 experimental units. The doses of ozone applied were 0, 0,35 and 0,45 ppm applied in pre-harvest and post-harvest. The indicators to be evaluated were pH, total solids, firmness and weight. The following results were obtained: the best harvest indices were Red and Pink because they presented better averages in each of the evaluated characteristics, reaching the last day of data collection with pH averages of 4,48 for Red and 4,31 for Pink. For total solids Pink carried an average of 3,3 ° Brix. In the variable Firmness Pink obtained an average of 2,6; as in weight, it obtained an average of 113,5 grams. The applied doses yielded positive results for 0,35 ppm reaching a weight of 120.9 grams; for firmness it obtained an average value of 2,5 in each fruit; in total solids it was an average of 3,1 ° Brix and in the variable pH it was 4,47. The best application method was postharvest immersion of the fruits, reaching average pH values of 4.4; in total solids it was an average of 3.3 ° Brix; for the variable Weight it was an average of 123 grams per fruit; while for firmness the best application treatment was for the fruits in pre-harvest with an average of 2,7. The economic analysis carried out allowed us to conclude that the treatment without ozone obtains a value of 3,76 usd of benefit for the producer, but the dose of 0,45 ppm that allows us to have benefits in the morphological characteristics obtained a value of 3,18 usd